PELUANG PENGUSAHAAN HUTAN LINDUNG DI KPHP BATULANTEH, PROVINSI NUSA TENGGARA BARAT Business Opportunities of Protection Forest in FMU of Batulanteh, West Nusa Tenggara Province - Fitta Setiajiati; Hardjanto .; Hendrayanto . (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Protection Forest in Indonesia is in critical situation. Several community activities threat the main functions of protection forest as watershed conservation. This study aimed to explore business opportunities of protection forest by investigating the potencies of wildlife, socio-economic, institution, actor interaction, and its contribution towards community’s livelihood. This research was conducted in surrounding protection forest in FMU Batulanteh, Sumbawa by field observation, semi structured interview, focus group discussion, literature study in August 2015 – November 2016. Combination among descriptive – participative – explorative approaches was used in data analysis. Protection forests contributed 33% for cash income and provided nutritious foods for local community, especially wild honey. FMU of Batulanteh could develop forestry business with community and other stakeholders in NTFPs manufacturing, especially wild honey, coffee, candle nut, herbal medicine and ecotourism business. Forestry extension and community empowerment are absolutely necessary for facilitating these businesses.Keywords: forestry business, forest contribution, livelihood, non-timber forest products, wild honey